School-IntegrIS: An Integrated System Approach to a School Management System of a State College in Northern Mindanao, Philippines - Grepon, Benzar Glen Sacragon; Labastida, Paul John A.; Vicariato, Zichri A; Sereñas, Caroline Laarni (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose  - With the increasing demands of system development in the school in terms of converting manual transactions into digital and computer-based systems, some systems and modules use independent URLs or subdomains in the school’s website that need to be memorized to access those systems. This project incorporates all independent systems into a single domain for easy access and user control. Method -  This study covers the system's primary functions, including its modules and subsystems, as well as the Agile Model research technique and methodology. Results  - The ISO/IEC 25010 quality evaluation system has been used to assess the project's functionality, efficiency, and usability. The project’s overall evaluation is 4.58, which indicates excellent performance based on a descriptive interpretation using a Likert scale for qualitative description. The initiative has been operational and hosted online using the school’s domain name with annually subscribed web hosting. Conclusion   -  The Integrated System meets the objectives per user requirements. The web application is well-recommended and acceptable to users. The system is cloud-hosted and is accessible 24/7 on the World Wide Web. With its implementation, personnel including students, can access their portals using one log-in credential, accessing multiple online services. Recommendations  - To ensure the project's longevity, future development should proceed consistently and integrate all systems, subsystems, and modules. New technologies should be incorporated to make the integrated system more adaptable to changes. Research Implications -  All systems, subsystems, and modules developed independently are incorporated into the study into a single, easily accessible integrated system periodically updated for continuous quality improvement. Practical Implications  - The main benefit of the Integrated system is that it can incorporate all school's independent systems into a single domain name and URL to avoid confusion about what to access, as it is already an enterprise-grade type of system.